Հասարակական կարծիքի ձևավորումը ԶԼՄ-ում ՀՀ ժողովրդավարացման պայմաններում - Դավթյան, Արգինա (YSU Journal of International Affairs, 2015)
The article reviews theoretical and contemporary significant problems concerning public opinion formulation through mass media in democratic conditions. As mass media is the main source for the public opinion in Armenia, it is obvious how significant the concepts of the freedom and productive activity of mass media, which are important for political processes. Meanwhile, the article reviews the principle concepts and conditions of productive activities of mass media, which plays the main role in the formulation of public opinion.
Keywords: democratization, concepts and conditions of productive activity of the mass media, subsidiation, public opinion, political processes